CRDS absorption spectrum of 17O enriched water vapor in the 12, 277–12, 894 cm−1 range. (December 2018) - Tan, Yan; Mikhailenko, Semen N.; Wang, Jin; Liu, An-Wen; Zhao, Xiao-Qin; Liu, Gu-Liang; Hu, Shui-Ming
Highlights: More than 1200 lines assigned to 18 RV bands of H2 17 O. About 420 vibration-rotational energies of H2 17 O and H2 16 O are newly obtained. The 5ν1 band of HD 17 O isotopologue is assigned for the first time. Several errors in H2 16 O line positions in the HITRAN-2016 are detected. Abstract: The absorption spectrum of water vapor enriched in oxygen-17 has been recorded by a continuous-wave cavity ring-down spectrometer (CW-CRDS) at room temperature in the 12, 277–12, 894 cm −1 region. The typical sensitivity of 2 × 10 −10  cm −1 allowed the detection of water vapor transitions with intensities larger than 1 × 10 −28  cm −1 /(molecule cm −2 ). In total, more than 3400 lines were observed in the recorded spectra with a typical frequency accuracy of 0.002 cm −1 . In which more than 3400 transitions were ro-vibrationally assigned to five water isotopic species (H2 17 O, H2 16 O, H2 18 O, HD 16 O, and HD 17 O) using the known empirical energy levels combined with the calculated variational line lists based on the results of Partridge and Schwenke. About 1300 transitions of H2 17 O were assigned, leading to the determination of new energy levels of 17 vibration states. Those assigned H2 17 O transitions are involved with the upper vibration states of (013), (023), (032), (051), (061), (070), (080), (090), (112), (131), (150), (160), (211), (230), (301), (310), and (320). The maximum values of the rotational numbers J and K a were 16 and 9, respectively. The 5ν1 band of HD 17 O was assigned for the first time as well. The line positions and energy levels determined in this work were compared with literature, and it shows a significant improvement of the line positions of H2 17 O and HD 17 O in the 12, 277–12, 894 cm −1 region.